Babesia bovis contains an abundant parasite-specific protein-free glycerophosphatidylinositol and the genes predicted for its assembly - Rodriguez, Anabel Elisa (2010)
Autonomous glycosylphosphatidylinositol (GPI) molecules (also protein-free GPIs or free GPIs) have been reported to be particularly abundant in some parasitic protozoa and mediate strong immunomodulatory effects on the host immune system. In the work at hand we have investigated the existence of free GPIs in B. bovis. Comparative thin layer chromatographic analysis of the protein-free glycolipid fraction of in vitro cultured B. bovis merozoites and erythrocyte membranes demonstrated the presence of an abundant parasite-specific band. Its chemical analysis revealed a GPI species containing a chain of two mannose residues, N-glucosamine and non-acylated inositol. The lipid moiety linked to inositol was diacylglycerol. The total fatty acid composition showed predominantly long-carbon chain molecules (12 % of C22:0 and 45% of C24:0). The potential of B. bovis to assemble the presented free GPI species was verified by the existence of seven genes in its genome that putatively encode the following GPI biosynthetic enzymes:  PI N-acetyl-GlcN-transferase (PIG-A and GPI-1), N-acetyl-GlcN-PI-de-N-acetylase (PIG-L), acyltransferase (PIG-W), dolichyl-phosphate mannosyl transferase (DPM-1), GPI mannosyltransferase I (PIG-M), and GPI mannosyltransferase II (PIG-V). GPI biosynthesis is vital for the intraerythrocytic parasite stage as mannosamine, an inhibitor of GPI biosynthesis, impaired in vitro growth of B. bovis merozoites. Absence of the vast majority of N-glycan metabolism encoding genes in the B. bovis genome underscores that the growth inhibitory effect of mannosamine is attributable to its interference with GPI biosynthesis and not with assembly of N-linked oligosaccharides, as has been described for higher eukaryotes. Elucidation of the structure and biosynthesis of GPI may allow to facilitate the development of future immune interventions against bovine babesiosis.